Safety and tolerability of a 2009 trivalent inactivated split‐virion influenza vaccine in infants, children and adolescents. Issue 5 (2nd April 2013) - Lambert, Stephen B.; Chuk, Lai‐man R.; Nissen, Michael D.; Nolan, Terry M.; McVernon, Jodie; Booy, Robert; Heron, Leon; Richmond, Peter C.; Walls, Tony; Marshall, Helen S.; Reynolds, Graham J.; Hartel, Gunter F.; et al.
<x xml:space="preserve">Abstract</x> Objective To evaluate the safety of CSL's split‐virion inactivated trivalent 2009 Southern Hemisphere formulation influenza vaccine (TIV) in children. Methods We enrolled 1992 healthy children into three groups: Cohorts A, ≥6 months to <3 years; B, ≥3 years to <9 years; and C, ≥9 years to <18 years. Children received one or two doses of 0·25 ml (22·5 μg haemagglutinin) or 0·5 ml (45 μg) TIV, depending on age and prior vaccination history. We collected post‐vaccination solicited adverse event (AE) data (days 0–6), including fever (temperature: ≥37·5°C axilla, ≥38·0°C oral), unsolicited AEs (days 0–29) and serious AEs (SAEs) and new‐onset chronic illnesses (NOCIs; to day 180 after last vaccination). Results At least one solicited AE was reported by 80%/78%/78% of children in Cohorts A, B and C, respectively. Systemic AEs were more common among Cohort A (72% of participants), and local AEs were more common among Cohort C (71% of participants). Fever was more common in younger cohorts, in influenza vaccine‐naïve children (29% of Cohort A receiving their first dose), and following first compared with second doses. Severe fever following a first dose prevented 20 participants receiving their second scheduled vaccine dose. A 7‐month‐old participant had a single uncomplicated febrile convulsion on the day of vaccination. Conclusions Nearly 80% of subjects reported at least one solicited AE following immunization. Fever prevalence was highest in vaccine‐naïve Cohort A participants, similar to other paediatric studies using CSL vaccine. Further research to understand fever‐related AEs in children following CSL's TIV is recommended.